(untitled) (Ameghiniana, 2013)
THE SISTEMATIC STATUS OF SOME MUROIDS STUDIED BY AMEGHINO IN 1889. REVALIDATION OF THE GENUS NECROMYS (MAMMALIA, RODENTIA, CRICETIDAE). The systematic status of seven Cricetidae species from the Quaternary of the Pampean Region (Argentina) previously mentioned and illustrated by Ameghino (1889), is clarified. After a study of the original remains, materials referred to: (1) Oxymicterus rufus fossilis, (2) Habrothrix arenicola,(3) Hesperomvs tener,(4) Tretomys atavus,(5) Calomys auritus and (6) Holochilus multannus; were determined as: (1) Rattus norvegicus, (2) Calomys musculinus, (3) Calomvs laucha, (4) Reithrodon auritus, (5) Akodon azarae and (6) Holochilus brasiliensis, respectively. Of the remains attributed by Ameghino to his genus Necromys, one is placed in A. a zarae, whereas a left maxilla cannot be distinguished, at the generic level, from A. amoenus, type species of the genus Bolomys Thomas, 1916. Necromys, synonymized with Calomys callosus by Hershkovitz (1962), regains validity, including as synonyms Bolomys and Cabreramvs Massoia and Fornes, 1967. The type species, N. conifer, preliminarly is considered as a nomen dubium. The biochron of Necromys would by early/middle Plioeene-Holocene in Buenos Aires Province.